Dog of discovery eaudiobook - Pringle, Laurence (Recorded Books Inc., 2014)
Picked by President Thomas Jefferson to explore the unknown wilds of the Louisiana Territory, Meriwether Lewis assembles a rugged team of adventurers, including co-captain William Clark-and a Newfoundland dog named Seaman. As hunter, retriever, and guard, Seaman becomes a trusted member of the Corps of Discovery. While the team tackles raging rivers and muddy shallows, Seaman is there-sharing their hunger and fatigue. Whether Indians threaten or grizzlies roar, he stands his ground. And through mountain peak or valley deep, Seaman remains a watchful friend and determined foe. Laurence Pringle-one of America's premier nonfiction writers for young people-has garnered critical acclaim for "turning natural history and science into page-turning reading" (Booklist). Relying on journal accounts, Pringle delivers a dog-centered narrative of the 8,000-mile Lewis and Clark expedition from its harrowing beginning to its triumphant end in 1806. To fill gaps in the historical record, Pringle imagines details of Seaman's vital role. ". a richly detailed . intriguing . treasure trove of information about the expedition and the dog that was its most unusual participant."-Library Journal "Full of adventure and excitement, this book contains a wonderful mix of intriguing stories and historical facts."-Childhood Education